Complaints related to occupational performance of adolescents who live HIV: subsidies for action of the Occupational Therapy - Cunha, Ana Paula Guimarães; Gontijo, Daniela Tavares (Revista de Terapia Ocupacional da Universidade de São Paulo, 2013)
The adolescence is a moment of biological, psychological and social transformation in associated with a HIV that when experienced with concomitant HIV infection, it can affect the occupational performance of infected adolescent. The objective of this study was to describe the relative’s complaints to the occupational performance of adolescents who live with HIV. This study carries out in a patients department of Diseases Infect Parasitic in Pediatrics, with 14 adolescents infected by HIV. The data were collected from the Canadian Occupational Performance Measure and analyzed from descriptive statistic. There was a total of 37 complaints related to occupational performance distributed in the categories of leisure, selfcare and productive. The highest number of complaints was observed in the category leisure. The study pointed subsidies for the planning of life quality promotion actions of the occupational therapy directed to adolescents and their caregivers.